Advance in the theory of ceramics/liquid metal systems wettability. Peculiarity of contact processes for transition and non—transition metals - Naidich, Y.V. (Адгезия расплавов и пайка материалов, 2013)
The review and some general comments devoted to scientific problems of high temperature wetting and adhesion in systems liquid metals—solid ceramic materials were done including the analysis of data received in a last time. The theoretical treatment of high temperature wetting processes and mechanism based on traditional thermodynamic notions and new approach on atomic and atomic-electron level were developed. As ceramics various substrates namely substrates with predominated ionic interatomic bonds (oxides for example) which usually hardly wetted by liquid metals are considered first of all. The contribution of nonequilibrium and equilibrium parts of adhesion to wetting process are considered and analysed. The ”active“ metals viz metals with high enough chemical affinity for solid phase atoms or iones were divided on transition metals (d-electron orbitals are partly occupied by electrons) and nontransition metals (dorbitals are empty or completely full by electrons). Зроблено огляд та подані деякі загальні коментарі, що стосуються наукових проблем високотемпературного змочування та адгезії у системах рідкі метали—тверді керамічні матеріали, включаючи аналіз одержаних останнім часом даних. Розроблені теоретична трактовка процесів високотемпературного змочування та механізм, що базується на традиційних термодинамічних уявленнях, і також новий підхід на атомному та атомно-електронному рівні. У першу чергу як кераміка розглянуті різні субстрати, а саме, субстрати, де переважають іонні міжатомні зв’язки (наприклад, оксиди), котрі звичайно погано змочуються рідкими металами. Розглянуто й проаналізовано внесок у процес змочування нерівноважної та рівноважної складових адгезії. “Активні” метали, а саме, метали з досить високою хімічною спорідненістю до атомів твердої фази або іонів розділені на перехідні метали (d-електронні орбіталі частково заповнені електронами) та неперехідні метали (d-орбіталі не заповнені або цілком заповнені електронами). Сделан обзор и представлены некоторые общие комментарии, касающиеся научных проблем высокотемпературной смачиваемости и адгезии в системах жидкие металлы-твердые керамические материалы, включая анализ полученных в последнее время данных. Разработаны теоретическая трактовка процессов высокотемпературной смачиваемости и механизм, основанный на традиционных термодинамических представлениях, и новый подход на атомном и атомно-электронном уровне. В первую очередь в качестве керамики рассмотрены различные субстраты, а именно, субстраты с преобладающими ионными межатомными связями ISSN 0136-1732. Адгезия расплавов и пайка материалов, 2013. Спецвып. 46 53 (например, оксиды), которые обычно плохо смачиваются жидкими металлами. Рассмотрен и проанализирован вклад в процесс смачивания неравновесной и равновесной составляющих адгезии. “Активные” металлы, а именно, металлы с достаточно высоким химическим сродством к атомам твердой фазы или ионам разделены на переходные металлы (d-электронные орбитали частично заполнены электронами) и непереходные металлы (d-орбитали не заполнены или полностью заполнены электронами).